Artificial selections for death‐feigning behavior in beetles show correlated responses in amplitude of circadian rhythms, but the period of the rhythm does not. (29th March 2022) - Miyatake, Takahisa; Abe, Masato S.; Matsumura, Kentarou; Yoshii, Taishi
Abstract: One of the most important survival strategies of organisms is to avoid predators. Studying one of such strategies, namely, death‐feigning behavior, has recently become more common. The success or failure of this antipredator strategy will be affected by the circadian rhythms of both prey and predator because death feigning sometimes has a diurnal rhythm. However, few studies have analyzed the effects of differences in circadian rhythms on predator‐avoidance behavior at the genetic level. Recently, the relationship between genes relating to circadian rhythm and death‐feigning behavior, an antipredator behavior, has been established at the molecular level. Therefore, in this study, we compared three circadian rhythm‐related traits, the free‐running period of rhythms, amplitude of circadian rhythms, and total activity of strains of three Tribolium species that were artificially selected for the death‐feigning duration: short (S‐strains) and long (L‐strains) durations. As a result, the amplitude of circadian rhythms and total activity were significantly different between S‐ and L‐strains, but there was no difference in the free‐running periods of the rhythm between the strains in T .  castaneum, T .  confusum, and T . freemani . Although the relationship between death‐feigning behavior and activity has been reported for all three species, a genetic relationship between the duration of death feigning and the amplitude of circadian rhythms has been newly found in the present study. It is important to investigate the relationship between antipredator strategies and circadian rhythms at the molecular level in the future. Abstract : We compared three circadian rhythm‐related traits, the free‐running period of rhythms, amplitude of circadian rhythms, and total activity of the strains of three Tribolium species that were artificially selected for the death‐feigning duration: short (S‐strains) and long (L‐strains) durations. As a result, the amplitude of circadian rhythms and total activity significantly differed between S‐ and L‐strains, but there was no difference in the free‐running periods of the rhythm between the strains, in T .  castaneum, T .  confusum, and T .  freemani . Although the relationship between death‐feigning behavior and activity has been reported for all three species, a genetic relationship between the duration of death feigning and the amplitude of circadian rhythms has been newly found in the present study.